Entrepreneurial Orientation and Digital Technology Adoption Intentions among Small Businesses in India - Srivastava, Kavisha Mahendra (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The rapid development of the digital economy has encouraged small businesses to adopt digital technologies in order to enhance their competitiveness and operational efficiency. However, the adoption of digital technologies among small businesses remains uneven, particularly in emerging digital economies. This study aims to examine the influence of entrepreneurial orientation dimensions—innovativeness, proactiveness, and risk-taking—on the intention to adopt digital technologies among small businesses. The research employs a quantitative approach using survey data collected from small business owners and managers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement model and the structural relationships between variables. The results indicate that innovativeness, proactiveness, and risk-taking have positive and significant effects on the intention to adopt digital technologies at a 10% significance level. These findings suggest that small businesses with stronger entrepreneurial orientation are more likely to embrace digital technologies as part of their business strategies. Innovativeness encourages firms to explore new technological solutions, proactiveness enables them to anticipate market opportunities and respond to environmental changes, while risk-taking reflects the willingness to invest in uncertain but potentially beneficial digital initiatives.